2012
DOI: 10.9738/cc125.1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Course After Emergency Colorectal Surgery for Secondary Peritonitis in the Elderly Is Often Complicated by Delirium

Abstract: Postoperative delirium, morbidity, and mortality in our elderly patients with secondary perionitis of colorectal origin is described. This is a chart-based retrospective analysis of 63 patients who were operated on at the University Hospital Basel from April 2001 to May 2004. Postoperative delirium occurred in 33%. Overall morbidity was 71.4%. Surgery-related morbidity was 43.4%. Mortality was 14.4%. There was no statistical significance between delirium, morbidity and mortality (P = 0.279 and P = 0.364). Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Ansaloni et al reported a lower incidence of delirium (18%) after acute surgery whilst other reported delirium rates in 33% in elderly patients (>70 years) with secondary peritonitis [12,23]. The wide range in these reported series may be explained by variations in included patient populations and the application of other diagnostic tools and procedure.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Ansaloni et al reported a lower incidence of delirium (18%) after acute surgery whilst other reported delirium rates in 33% in elderly patients (>70 years) with secondary peritonitis [12,23]. The wide range in these reported series may be explained by variations in included patient populations and the application of other diagnostic tools and procedure.…”
Section: Discussioncontrasting
confidence: 49%
“…Older patients undergoing acute abdominal surgery are also at risk for postoperative delirium [12]. However, to our knowledge the incidence of postoperative delirium and the associated morbidity and mortality after emergency colon surgery in the elderly has not been reported yet.…”
Section: Introductionmentioning
confidence: 82%
“…Postoperative delirium (PD) is an acute, fluctuating disorder of attention and cognition [1]. It is one of the most common serious postoperative complications in elderly patients, with a reported incidence of 9.0-13.2% in gastrointestinal and general surgery [2][3][4][5], 33% in colorectal emergency surgery [6], 9.1-28.6% in orthopedic surgery [7][8][9], and 23.0-32.0% in cardiovascular surgery [10,11]. In addition to being subjectively uncomfortable, PD is associated with accidental removal of drains or catheters, worsened treatment compliance, exhaustion of medical staff, and medical accidents such as falls.…”
Section: Introductionmentioning
confidence: 99%
“…PD is also associated with impaired treatment outcomes, including impaired activities of daily living [7], prolonged hospitalization [2,3,5] and intensive care unit stays [2], elevated morbidity [2,3,6] and mortality [9,12,13] and increased hospital costs [2].…”
Section: Introductionmentioning
confidence: 99%
“…6 The incidence of delirium has been noted to be as high as 60% in all inpatients and 7%−35% within the general surgery population. [6][7][8][9][10][11] The consequences of delirium result in substantial health care expenditure owing to a prolonged hospital stay and increased disability, necessitating escalated levels of care at discharge. [12][13][14][15] Delirium is also associated with increased mortality rates during the hospital stay and substantially increased overall 6-month and 1-year mortality rates.…”
mentioning
confidence: 99%